A Critical Study of Abba Ho PatÄ“r in Romans 8:15 in the New Revised Asante Twi Version (2018) - Asamoah, Emmanuel Foster; Adjei-Fianko, Diana (European Scientific Journal, ESJ, 2021)
Bible translation is among the difficult exercises in scholarship because it demands a careful analysis of the biblical text from the source language into the target language. The religio-cultural settings and worldview of the indigenous people are also considered so that they are able to access the word of God as written and meant by the author(s). An example of Bible translation exercise is the New Revised Asante Twi Version (NRATV) 2018, which contains some translation problems. Some texts are not translated but â€œcarried whollyâ€ into the new or target language to make them look as if they form part of the native language. One of such is â€œAbba,â€ which is a HebraicAramaic word found in Romans 8:15. Since Abba is not an Asante (and Akan) language, it becomes difficult for the Asante reading community (and by extension all Akan languages) and users of the Asante-Twi Bible to understand and express the concept within their religio-cultural worldview because they do not understand the thought of the author in their language. Using exegetical, mother-tongue hermeneutics and the communicative method of translation as approaches, the study has found out that the translation of â€¦Î‘Î²Î²Î± á½ Ï€Î±Ï„Î®Ï (â€¦Abba ho PatÄ“r) as â€¦Abba, Agya (â€¦Abba, Father) in the Asante-Twi Bible (2018) should be rendered as â€œâ€¦Agya, Mâ€™agyaâ€ (Father, My Father). The study has thus added to the interpretations of Romans 8:15 in Asante-Twi. It is being recommended that in the future revision of the Asante-Twi Bible, the Bible Society of Ghana should consider using â€œâ€¦Agya, Mâ€™agyaâ€ (Father, My Father) in the translation of â€¦ Î‘Î²Î²Î± á½ Ï€Î±Ï„Î®Ï (â€¦Abba ho PatÄ“r).